Spin-orbit entangled moments and magnetic exchange interactions in cobalt-based honeycomb magnets BaCo2(XO4)2 (X = P, As, Sb) - Subhasis Samanta; Fabrizio Cossu; Heung-Sik Kim (npj Quantum Materials)
Abstract Co-based honeycomb magnets have been actively studied recently for the potential realization of emergent quantum magnetism therein such as the Kitaev spin liquid. Here we employ density functional and dynamical mean-field theory methods to examine a family of the Kitaev magnet candidates BaCo2(XO4)2 (X = P, As, Sb), where the compound with X = Sb being not synthesized yet. Our study confirms the formation of Mott insulating phase and the J eff = 1/2 spin moments at Co2+ sites despite the presence of a sizable amount of trigonal crystal field in all three compounds. The pnictogen substitution from phosphorus to antimony significantly changes the in-plane lattice parameters and direct overlap integral between the neighboring Co ions, leading to the suppression of the Heisenberg interaction. More interestingly, the marginal antiferromagnetic nearest-neighbor Kitaev term changes sign into a ferromagnetic one and becomes sizable at the X = Sb limit. Our study suggests that the pnictogen substitution can be a viable route to continuously tune magnetic exchange interactions and to promote magnetic frustration for the realization of potential spin liquid phases in BaCo2(XO4)2.